2016 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2016
DOI: 10.1109/smc.2016.7844604
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing human perception of emergent swarm behaviors

Abstract: Abstract-Human swarm interaction (HSI) involves operators gathering information about a swarm's state as it evolves, and using it to make informed decisions on how to influence the collective behavior of the swarm. In order to determine the proper input, an operator must have an accurate representation and understanding of the current swarm state, including what emergent behavior is currently happening. In this paper, we investigate how human operators perceive three types of common, emergent swarm behaviors: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…An important issue for the supervision of a semiautonomous swarm is the possibility to efficiently convey information about the swarm's current state, its future states, and the effects of human input on its behavior. This work originates from the recent key contributions to human-swarm interaction [5,[9][10][11][12][13][14] and the use of nonverbal communication from robots [15][16][17][18][19]. Both domains are discussed in this section, leading to the key concept of the cohesion of a swarm for group-level perception of motion.…”
Section: Expressive Behavior Of Robotic Swarmsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important issue for the supervision of a semiautonomous swarm is the possibility to efficiently convey information about the swarm's current state, its future states, and the effects of human input on its behavior. This work originates from the recent key contributions to human-swarm interaction [5,[9][10][11][12][13][14] and the use of nonverbal communication from robots [15][16][17][18][19]. Both domains are discussed in this section, leading to the key concept of the cohesion of a swarm for group-level perception of motion.…”
Section: Expressive Behavior Of Robotic Swarmsmentioning
confidence: 99%
“…Humans are generally good at recognizing patterns of collective motion [13]. However, because human attention can fluctuate and the capacity of humans working mem-ory is limited, the number of robots a single operator can control is also limited [12,21].…”
Section: Human-swarm Interactionmentioning
confidence: 99%
“…Participants found it awkward when they were requested to provide unanchored and arbitrary parameters and received feedback in the form of paths which might fail to reach the goal (incomplete) or a message indicating them to be invalid. Participants may prefer real-time interaction methods for switching between behaviors as in [10], [11] rather than preplanning a complete behavior sequence which places greater demands on working memory and decision making. We are considering adding intermediate goal functions to shorten the feedback loop and make the process more controllable for users.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have proven that this phenomena, they term neglect benevolence, exists for all LTI (linear time invariant) systems [4] and that human participants can learn to approximate optimal switch times between swarm behaviors although their responses almost always precede the optimal time [9]. While control of a library of behaviors and the ability to specify their parameters provide an extraordinary degree of control over a swarm, humans have difficulty in recognizing swarm states [10] and predicting the effects of their interventions [11] as well as the timing of their actions [9], making unaided control difficult and inefficient. The problem of behavior composition is extremely difficult even for a computer because of the large space of alternative behaviors and durations that must be searched.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature on human-robot trust, has found that trust is influenced primarily by the perceived performance of the robot [8]. However, task performance of swarms is often not intelligible to the operator [25], [28], since swarms perform tasks through complex interactions among the swarm members themselves, such as consensus that takes time to converge. For example, the swarm may not follow the operator's command in a case where it first needs to maintain connectivity which may not be readily apparent to the operator.…”
Section: Introductionmentioning
confidence: 99%